The influence of Perceived Organizational Support (POS) toward Turnover Intention of Bank Central Asia (BCA) employee, The mediating effect of Organizational Commitment - admin, Fajar Kempas Adi Nugraha B1024161007 (Jurnal Manajemen Update, 2021)
The purpose of this research is to analyze the impact of Perceived Organizational Support and Organizational Commitment toward Turnover intention of the employees and to test the mediating effect of Organizational commitment toward Turnover Intention in Banking company, BCA KCU Kubu Raya. Nowadays, the competitive business world has considered that an important task to manage employee turnover for any organization especially in Banking sector as it is known that employee from banking sector tend to be turnover from their job. The role of support from organization has known to reduce the intention of turnover from employees and make them tends to be commit with their organization.Â  From this point we can see that it is undeniable Perceived Organizational Support as an important factor in every company and Organization, especially in Banking sector. In this research, the data analysis method used is Structural Equation Model Partial Least Square (SEMPLS) method. To conduct analysis using PLS method, this research is using SmartPLS 3.0 software. The hypothesis of the research are H1 : POS have a significant influence on organizational commitments H2 : POS have significant influence on turnover intention H3 : Organizational Commitments have a significant influence turnover intentions. H4 : Organizational Commitments mediate the relationship between POS and turnover intentions. The result of this research shows that all of the Hypothesis Are Accepted.